“A SPACE FOR THE TRANSLATOR(S)”: SITUATING STUDENT TRANSLATORS IN REAL-LIFE SHOES (Journal of Contemporary Philology, 2020)
The paper presents an extra-curricular project of translating a collection of short stories Prostor za mokrog psa (2011) into English. The translation was done by 15 Niš English Department BA and MA students from February to July 2017, resulting in a publication (The place for the wet dog 2018). Starting from the theoretical concept of Situated Translation (Risku 2002), a Cognitive Sciences approach which ‘portray[s] translation as a highly complex and ill-structured social, cognitive, and cultural process’ (Kiraly 2005: 1103), the study presents the results from the comparison of various versions of the student translations and informal comments during group and individual conferences. In operationalizing the theory in translation education, we use the ‘empowerment’ approach (Kiraly 2005), which helps students become ’proactive agents of their own learning through authentic, collaborative work leading to autonomy and expertise’ (ibid, 1104). We focus on the problems concerning the issues of audience (how to reach foreign readership), cultural and historical context of the stories (understanding of the ex-Yugoslav context) and translating different dialects, sociolects and idiolects. Although an extra-curricular activity, the project proves that the authentic, ‘situated’ translation tasks greatly contribute to students’ learning and competences development, preparing students for real-life tasks.
Keywords: translation; situated translation; socio-cultural concepts; student projects; extracurricular student learning